2016
DOI: 10.1177/0269881116662634
|View full text |Cite
|
Sign up to set email alerts
|

Survey study of challenging experiences after ingesting psilocybin mushrooms: Acute and enduring positive and negative consequences

Abstract: Acute and enduring adverse effects of psilocybin have been reported anecdotally, but have not been well characterized. For this study, 1993 individuals (mean age 30 yrs; 78% male) completed an online survey about their single most psychologically difficult or challenging experience (worst “bad trip”) after consuming psilocybin mushrooms. Thirty-nine percent rated it among the top five most challenging experiences of his/her lifetime. Eleven percent put self or others at risk of physical harm; factors increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
380
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(413 citation statements)
references
References 30 publications
25
380
3
5
Order By: Relevance
“…Difficult experiences are not necessarily pathological and can be understood as part of the therapeutic process (e.g. working through cancer-related psychological or existential distress through challenging encounters or emotionally charged confrontations with cancer-related fearful imagery or symbolism) (Carbonaro et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Difficult experiences are not necessarily pathological and can be understood as part of the therapeutic process (e.g. working through cancer-related psychological or existential distress through challenging encounters or emotionally charged confrontations with cancer-related fearful imagery or symbolism) (Carbonaro et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Within empirical studies, individuals who are high in neuroticism may be either explicitly (as in Studerus et al, 2012) or implicitly screened out of the study. Also, aspects of the environment such as interpersonal support that may mitigate challenging experiences are present by design in experimental laboratory settings (as in Griffiths, Richards, McCann, & Jesse, 2006; Johnson, Richards, & Griffiths, 2008; Studerus et al, 2012), but are variable and in many cases absent during experiences analyzed in the current report (Carbonaro et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Responses from a total of 1993 participants who provided useable data for an online survey of challenging experiences with psilocybin (Barrett et al, 2016; Carbonaro et al, 2016) were included in the current analyses. Analysis of Study 1 data constitutes a secondary analysis of previously reported data (Barrett et al, 2016; Carbonaro et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, controlled research has found that certain personality traits, e.g., ‘absorption’ and ‘neuroticism’ can predict the intensity and quality of a psychedelic experience (Studerus et al, 2012; Carhart-Harris et al, 2015, 2018; Carbonaro et al, 2016; Barrett et al, 2017) while readiness to ‘let go’ and quality of the environment also seems to be predictive of response (Carhart-Harris et al, 2018). In a similar fashion, the prevalence and nature of NDEs appear to be sensitive to environmental, demographic and personality variables, such as etiology and prognosis of the NDE, age, absorption and a propensity to report paranormal experiences (Kohr, 1983; Greyson, 2003).…”
Section: Introductionmentioning
confidence: 99%